An intellectual adventurer in archaeology : reflections on the work of Charles Thomas - Jones, Andy M.,; Quinnell, Henrietta, (Archaeopress Publishing Ltd, 2018)
Charles Thomas (1928-2016) was a Cornishman and archaeologist, whose career from the 1950s spanned nearly seven decades. This period saw major developments that underpin the structures of archaeology in Britain today, in many of which he played a pivotal part. He campaigned for the Chair of Cornish Studies at the University of Exeter, which he then held from 1972 until retirement, after teaching archaeology at Edinburgh and Leicester Universities. The 'Intellectual Adventure in Archaeology' was to Charles the mental stimulation of developing narratives for the past, especially in the areas in which he was a leading authority, including the early church in Britain, the early medieval period more generally, and Cornish studies. The contributions to this volume demonstrate the extent to which his scholarship and character has underpinned the work of others, in Cornwall and beyond.